NATION-FORMATION EX NEGATIVO – LITERARIZED COMMUNITIES OF SUFFERING AFTER THE ECOCIDE - Günther, Clemens (Porównania, 2019)
Clemens Günther, NATION-FORMATION EX NEGATIVO – LITERARIZED COMMUNITIES OF SUFFERING AFTER THE ECOCIDE. “PORÓWNANIA” 1 (24), 2019. Vol. XXIV, P. 95-110. ISSN 1733-165X. The article addresses the possibility of the cultural creation of national identity in the former Soviet republics of Belarus and Kazakhstan which have been affected by ecological catastrophes (Chernobyl and the Aral Sea). In the beginning, it gives an overview on the shifting cultural responses to catastrophes in late Socialism before generally discussing the possibility of giving meaning to catastrophes. In its main analysis, it focuses on Svetlana Aleksievich’s Chernobyl Prayer and Abdizhamil Nurpeissov’s The dying lake and their respective means of giving meaning to time, space and social bonds which have been transformed through the ecocide.